Implementation Classification Of Hospital Class And Humanist Standard Inpatient Class In Purwakarta - Trisaksono, Ario; Harun; Rizka (GoAcademica Research & Publishing, 2023)
The government has established provisions for classification of hospital classes and standard class inpatient care in 2020. With these provisions, all hospitals are required to immediately implement and adjust the infrastructure they have. However, not all hospitals have adjusted according to the stipulated provisions. For this reason, readiness research needs to be carried out from each hospital in Purwakarta , regarding the implementation of hospital class classification and the implementation of standard class inpatient care. Method research carried out , use type Study Quantitative Descriptive of 4 hospitals in Purwakarta regarding the inpatient facilities they have. Implementation of Hospital class classification for research objects in Purwakarta is 75% underway. Meanwhile, the implementation of standard class inpatient care is still not fully implemented. Because there is no clarity on implementation and there are no strict sanctions for these regulations. The role of the Government through the Health Service is very much needed to enforce the implementation of the regulations, so that sanctions against hospitals will run well and the review process for determining hospital classes can be carried out. The government's regulatory function must be carried out by preparing clear and specific derivative regulations to guard the regulatory mandate. So that the benefits of health services for the community can be felt and the elements of justice and the absence of differentiation in services will be enjoyed by all people.